Justice and politics in energy access for education, livelihoods and health: How socio-cultural processes mediate the winners and losers. (June 2018) - Kumar, Ankit
Highlights: This paper evaluates education, livelihoods and health goals of energy access. Pre-exiting socio-cultural processes mediate development outcomes of energy access. Gender, socio-economic positions and local economy vital links between development and energy. Projects providing electricity (rather than just lighting) might lead to better social outcomes. Less privileged may benefit if projects are designed with socio-cultural process in mind. More studies on how local socio-cultural processes mediate the impacts of development and energy projects required. Abstract: The rhetoric on development benefits of energy access often focuses on education, livelihoods and health. Using case studies of two energy access projects in India, this paper demonstrates that these claims, while true in part, are neither simple nor straightforward. It argues that pre-existing socio-cultural processes mediate the development outcomes of energy access projects. In particular, the roles of gender, socio-economic positions and the local economy are vital in understanding the links between education, livelihoods, health and energy. This paper is important for two reasons. First, working with culture as a mediator, it provides nuanced insights into relationships between energy access and three key development goals. Second, by presenting this analysis, the paper identifies a need for further research on the relationships between socio-cultural processes, development and energy access and, how by keeping these processes in mind, the benefits of energy access could be extended to less privileged social groups. This paper is based on a nine-month long ethnographic research in five villages in India's Bihar state. Home tours, interviews, participant observations and group discussions were used to collect the data.